Keterpaduan Standar Kompetensi dan Desain Pembelajaran pada Mata Pelajaran Pendidikan Agama Islam di SMA Islam Az-Zahrah Palembang - Arinda Rahmi Auliani; Muhamad Ilham Maulana; Muhamad Fauzi; Widya Wulandari (STAI AL-AMIN, 2026)
This study aims to analyze the integration between Competency Standards and instructional design in the Islamic Religious Education subject at Az-Zahrah Islamic High School in Palembang. The study employed a descriptive qualitative approach using literature review and field research methods. Data were collected through observations and interviews with Islamic Religious Education teachers. The results show that the instructional design was developed in accordance with the Competency Standards set forth in the curriculum and implemented by adapting teaching methods based on student characteristics. However, challenges remain in implementation, particularly regarding differences in students’ ability to understand the material. Therefore, a variety of teaching methods is necessary to effectively achieve learning objectives. This study confirms that the integration of Competency Standards and instructional design is crucial for improving the quality of PAI instruction.